Microcontroller Based Stator Resistance Determination of Induction Motor on Temperature Variations - Siraj Ahmed T; Sukhdeo Sao; K.S.R Anjaneyulu (Institute of Advanced Engineering and Science, 2014)
In this paper an experiment has been conducted to determine the online stator winding resistance of an induction motor, in industries as well as domestic purpose induction motors is largely utilized, as it has both applications of variable and constant torque operation nature. The major requirement of an electric drive system is its independent control of torque and speed; this is achieved in DC motor Drive but has more disadvantages. With the help of fast acting switching devices it is possible to independently control an induction motor. To control an induction motor drive various methods are available, direct torque control of induction motor is one of the best method of control compared to other, the only disadvantage is the torque ripple. Stator resistance is one of the parameter for the cause; hence its determination is essential. An experiment is conducted at various loads on an induction motor and then the temperature in the stator winding is noted at different instants using microcontroller, from the tabulated readings stator winding resistance is calculated and compared with the direct measurement by Volt-Ampere method. Further it is suggested that by implementing the actual online value of stator resistance of an induction motor dive torque ripple can be minimized. DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5649